Profile of Student’s Scientific Literacy in Immune System Materials Through Problem Based Learning (PBL) - Isnaeni, Lili Astuti; Susanti, R.; Dewi, Nur Kusuma (Journal of Innovative Science Education, 2021)
This study aims to analyze profile of students' scientific literacy in immune system material seen by aspects of competence (science process), content (knowledge), and context (application) through problem-based learning (PBL). This study used an experimental method, namely one shot case study design. The population used in this study is class XI SMAN 1 Palimanan with a research sample of class XI MIPA 1,2,3,6 amount of 134 students. Instrument used a reasoning multiple choice test sheet to measure students' scientific literacy profiles and interview sheet to add data the results of the scientific literacy test. Sub-material used the concept of immune system material and its application. The results showed that contained on 4 students (2.99%) in very high category of scientific literacy, 22 students in high category (16.42%), 63 students in medium category (47.01%), 18 students in low category ( 13.44%) and 27 students in very low category (20.14%). Indicators explaining scientific phenomena can be achieved well with the number of students 45 and the proportion of achievement is 33.58%; scientific scientific survey can be achieved well with the number of students 53 and the proportion of achievement is 39.55% .; interpret data and scientific evidence well with the number of students 49 and the proportion of achievement is 36.57%. Based on the results of the study, it can be concluded that students' scientific literacy is in the medium group.